Proceedings of the 5th International ICST Conference on Pervasive Computing Technologies for Healthcare 2011
DOI: 10.4108/icst.pervasivehealth.2011.245965
|View full text |Cite
|
Sign up to set email alerts
|

Purposeful social media as support platform: Communication frameworks for older adults requiring care

Abstract: Abstract-Despite more and more people adopting Social Networking Sites (SNSs) such as Facebook, adults over 65 years of age still make up a relatively small percentage of those numbers. A perceived lack of purpose is suggested as one of the key issues surrounding the lack of interest of older adults, yet with health benefits associated with usage, such as increased social capital and community belonging, there is a unique opportunity present to develop social media that help carers stay in touch with patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Studies show that online social networks and support groups benefit a wide range of transitional communities, such as new parents [20], those who have recently lost a job [11], adults transitioning to old age [37], and students entering college [19,39,41,43]. In the absence of socialization that allows people to gain the skills necessary to smoothly navigate life transitions [25], some of these skills are learned via SNS networks.…”
Section: Related Workmentioning
confidence: 99%
“…Studies show that online social networks and support groups benefit a wide range of transitional communities, such as new parents [20], those who have recently lost a job [11], adults transitioning to old age [37], and students entering college [19,39,41,43]. In the absence of socialization that allows people to gain the skills necessary to smoothly navigate life transitions [25], some of these skills are learned via SNS networks.…”
Section: Related Workmentioning
confidence: 99%
“…The majority of research has focused on younger age groups such as teenagers and university students. Despite the increase in adoption rates of SNS's by senior citizens, not much is known yet regarding reasons and motivations for adoption and use within this age category [16] [17] [18]. Previous research suggests issues such as perceived lack of usefulness, ease of use as well as privacy and security concerns as key factors contributing to the slower adoption rates by senior citizens [16] [18].…”
Section: Senior Citizens and Technology Usementioning
confidence: 99%
“…Despite the increase in adoption rates of SNS's by senior citizens, not much is known yet regarding reasons and motivations for adoption and use within this age category [16] [17] [18]. Previous research suggests issues such as perceived lack of usefulness, ease of use as well as privacy and security concerns as key factors contributing to the slower adoption rates by senior citizens [16] [18]. Senior citizens are influenced by their social peers and members of their family, particularly their children and grandchildren who play the role of change agents in creating awareness and ultimately the use of the technology [19].…”
Section: Senior Citizens and Technology Usementioning
confidence: 99%
“…The investigation by Norval et al [48] suggested the use of an established online social network, like Facebook, as a framework for telecare, i.e. for communication to help carers stay in touch with patients and provide support when needed.…”
Section: Online Social Media Platforms and Healthcarementioning
confidence: 99%